Association between corporate governance practices and firm performance of manufacturing companies in Sri Lanka - Samanmali, I.M.S.I.; Perera, P.R.M.R. (Faculty of Commerce and Management Studies, University of Kelaniya Sri Lanka, 2022)
Effective corporate governance procedures are thought to be crucial for lowering investor risk, attracting in investment money, and enhancing company performance. However, depending on the economic, political, and social circumstances, corporate governance systems differ from one nation to the other. Agency theory, which emphasizes the division of ownership and control, served as the theoretical foundation for this investigation. This study explains how the board structure of Sri Lankan manufacturing companies affected business performance. Mainly Five Corporate Governance components were used in this study, such as Board Size, Board Independence, Audit Committee Composition, Gender Diversity and CEO Duality. Board Size refers to the number of board members in the Board. CEO Duality refers to the separation of the CEO and chairman roles; board composition refers to the Independence non executive directors on the board; Audit committee Composition refers to the number of directors in the Audit Committee and Gender diversity refers to the Female directors in the Board. Furthermore, the firm performance is measured by accounting base measurements (ROA) This study considered all Manufacturing Companies listed in the Colombo Stock Exchange from 2019 to 2022. It also looks at how corporate governance practices and business performance relate to each other. Each company's annual report served as the source for all the data gathered and analyzed using correlation, and panel regression analysis. This study contributes significantly to the body of knowledge on corporate governance in developing nations and illustrates the relationship between corporate governance and firm performance. This study supports the agency theory claiming that effective corporate governance measures increase boards' shareholder accountability and improve business performance.
Keywords: Return on Asset, Return on Equity, Corporate Governance, Firm Performance